Analysis of Influence Employee Competenceand Job Satisfaction on Employee Performance with Employee Engagement as a Mediating Variable at PT. Perkebunan Nusantara XII Surabaya - Reggy Irawan Setiyobudi; Hary Sulaksono; Muhammad Firdaus (International Journal of Economics, Commerce, and Management, 2025)
This study aims to analyze the effect of employee competence and job satisfaction on employee performance, with employee engagement as a mediating variable at PT Perkebunan Nusantara XII Surabaya. Employee competence and job satisfaction are crucial factors in improving employee performance, while employee engagement plays a role in strengthening this relationship. This research adopts a quantitative approach using secondary data from employee competency measurement reports for the 2020-2022 period. The analysis method employed is Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The findings indicate that employee competence and job satisfaction have a positive and significant impact on employee performance. Furthermore, employee engagement has been proven to play a significant mediating role in the relationship between employee competence and employee performance, as well as between job satisfaction and employee performance. In other words, employees with high competence and job satisfaction tend to be more engaged in their work, ultimately enhancing their performance. These findings have practical implications for companies to improve employee competence and job satisfaction through training, fair incentive distribution, and creating a work environment that fosters employee engagement. This study also contributes to the development of human resource management theory, particularly regarding employee engagement as a mediating factor in enhancing employee performance.